Epidemiology of Canine Leptospirosis in Kuala Lumpur and Selangor - Phumoonna, Tongted (2001)
This study was conducted to determine the current state of leptospirosis in dogs in Kuala Lumpur and Selangor. The usefulness of several laboratory techniques was also evaluated for the diagnosis of leptospires and determination of leptospirosis prevalence. One hundred and sixty five serum samples were collected and examined for serological prevalence of leptospirosis. The dogs surveyed were classified into stray and pet groups. Pet dog samples were obtained from dogs which were brought to the University Veterinary Hospital at Universiti Putra Malaysia (UVH-UPM). Samples from stray dogs were obtained from Society for the Prevention of Cruelty to Animals (SPCA), and Paws Animals Welfare Society (PAWS). All serum samples were screened for leptospiral IgM and IgO antibodies, using an enzymelinked immunosorbent assay (ELISA). Then, these serum samples were re-examined for leptospiral antibodies and serovar-specificity by the microscopic agglutination test (MAT). A serum sample was confirmed to have leptospiral infection if its MAT titre was 2: 100, or IgM-ELISA titres of 2: 160, or IgO-ELISA titres of more than two times of negative controls, or any combination of the above. The study showed a high serological prevalence of leptospiral infection, particularly in the group of stray dogs. Leptospira pomona was found to be the most predominant serovar both in the pet and stray dogs. In previous surveys in 1 95 5, 1 96 1 , 1 979 and 1 986, the infection due to L. pomona was uncommon whilst L. icterohaemorrhagiae and L. canicola were reported to be predominant in dog populations in Malaysia. The emergence of L. pomona infection in dogs in Malaysia could be due to the only use of vaccines containing serovars icterohaemorrhagiae and canicola. Therefore, to prevent leptospiral infection in dogs and reduce the transmission of this disease from dogs to other animals and humans, serovar pomona should be included in the vaccines to be used in Malaysia. The bacterial culture revealed no leptospires in the dogs surveyed. This could possibly be due to the fastidious nature of the organisms, stage of infection, or level of antibodies in the circulating blood. However, twenty one unknown isolates were successfully detected in blood and urine samples of the dogs surveyed by the polymerase chain reaction (PCR) and identified by low-stringency PCR technique.